Kegawatan Sindrom Geriatri, Self Care Deficit, terhadap Kualitas Hidup Lansia - Irine Yunila Prastyawati; Widayani Yuliana (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Background: The proportion of the elderly population increases every year, resulting in a higher life expectancy, but also higher health care. The elderly often experience geriatric emergency syndrome problems so that it is closely related to the independence of the elderly in maintaining their health. Changes in the independence of the elderly bring real changes to the elderly in carrying out daily activities in certain social and cultural conditions where this condition puts the elderly at risk for changes in the quality of life.Objective: This study aims to identify the severity of geriatric syndrome, self care deficit on the quality of life of the elderly.Methods: This type of research is experimental observation with 100 respondents at UPTD Griya Werdha Jambangan Surabaya.Results: The Spearman rank correlation test showed that the severity of the geriatric syndrome was associated with the quality of life in the physical domain (0.011), psychological domain (0.000), and the environmental domain (0.000), while the social relationship domain (0.117) had no relationship with the severity of the geriatric syndrome. Self care deficit with the quality of life of the elderly is related to the psychological domain (0.014), while the physical domain (0.152), social relations (0.932) and the environment (0.227) have no relationship.Conclusion: The conclusion of this study is that there is a relationship between the severity of geriatric syndrome and the quality of life of the elderly in the physical, psychological, and environmental domains. There is a relationship between self care deficit with the quality of life of the elderly in the psychological domain.